Contribuições das Feiras de Matemática para o Desenvolvimento Profissional de professores que ensinam Matemática no Tocantins - Araujo, Vânia Silva (2024)
This research consisted of investigating the practices of teachers who teach Mathematics in the Final Years of Elementary School, mobilized by holding Mathematics Fairs in the school context of the Military College of the State of Tocantins - Jorge Humberto Camargo. To this end, we raised the following question as a research problem: In what terms do teaching practices mobilized at Mathematics Fairs contribute to the Professional Development of Teachers who Teach Mathematics? Given the concerns and research problems, the general objectives were to analyze the contributions of the Mathematics Fairs of the Military College of the State of Tocantins - Jorge Humberto Camargo - to the Professional Development of Teachers who Teach Mathematics. The methodological design of this research was based on a qualitative approach from the perspective of Case Study research, with analysis of Figures (produced by images of fairs held), documentary analysis (reports, plans and Pedagogical Political Project) and analysis of individual interviews carried out with five teachers participating in the research, with the theoretical lens of authors who research on Teaching Professional Development, Training of Teachers who Teach Mathematics and Mathematics teaching practices with the manipulation of concrete materials in Teaching Laboratory environments, Mathematics Clubs and Fairs Mathematics. These analyzes were carried out based on the understanding of the Fairs held in the years 2014 to 2019 presented through the Case Description Strategy, in order to meet the first specific objective of the research. Subsequently, an analysis of the corpus of this research was carried out using the Logical Model Analytical Technique, which sought to understand the elements of the Professional Development of Teachers who Teach Mathematics in the context of holding Mathematics Fairs, as well as reflecting on the contributions of these Fairs in the professional development of this teacher. As a result, three analytical categories emerged that allowed us to highlight practices that explain elements of Teaching Professional Development, namely: Improvement of Teaching Practice Development of Teaching Skills and Improvement of the Teaching and Learning Process. Of these teaching practices we can mention: collective planning and engagement of teachers in studies and research, use of diverse materials to teach Mathematics, development of pedagogical content knowledge, reflections on the teaching and learning process, development of teaching autonomy, among others practices and challenges that these teachers demonstrated when holding Mathematics Fairs in a school environment.